Microstructure of microemulsion modified with ionic liquids in microemulsion electrokinetic chromatography and analysis of seven corticosteroids. Issue 17 (2nd September 2013) - Ni, Xinjiong; Yu, Meijuan; Cao, Yuhua; Cao, Guangqun
<x xml:space="preserve">Abstract</x> In this work, the influences of ionic liquid (IL) as a modifier on microemulsion microstructure and separation performance in MEEKC were investigated. Experimental results showed that synergetic effect between IL 1‐butyl‐3‐methylimidazolium tetrafluoro‐borate (BmimBF4) and surfactant SDS gave a decreased CMC. With increment of IL in microemulsion, negative ζ potential of the microdroplets reduced gradually. The influence of IL on the dimensions of microdroplet was complicated. At BmimBF4 less than 8 mM, IL made microemulsion droplet smaller in size. While at BmimBF4 more than 10 mM, the size increased and reached to a maximum value at 12 mM, where the microdroplets were larger than that without IL. After that, the micreodroplet size decreased again. Relative fluorescence intensity of the first vibration band of pyrene to the third one (I1/I3) enhanced as IL was added to microemulsion, which indicated that this addition increased environmental polarity in the inner core of microdroplets. Prednisone, hydrocortisone, prednisolone, hydrocortisone acetate, cortisone acetate, prednisolone acetate, and triamcinolone acetonide were analyzed with MEEKC modified with IL to evaluate the separation performance. Cortisone acetate and prednisolone acetate could not be separated at all in typical microemulsion. The seven analytes could be separated by the addition of 10 mM BmimBF4 into the microemulsion system. The method has been used for analysis of corticosteroids in cosmetic samples with simple extraction; the recoveries for seven analytes were between 86 and 114%. This method provides accuracy, reproducibility, pretreatment simplicity, and could be applied to the quality control of cosmetics.